CURRENT STATE AND DEVELOPMENT TRENDS OF E-TRADE IN UKRAINE - YAROSLAVA, Larina; NAHORNA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the approaches of scientists to the definition of the essence of electronic commerce, the differences between the categories "electronic commerce" and "e-trade", considers modern approaches to trade based on digital marketing. The purpose of the article is to determinatе the essence and conditions of the development of e-trade since its inception, determination of the features of the current state and development trends, advantages and disadvantages of e-trade. To realize the set goal, the following tasks were set: clarify the categorical and conceptual apparatus in the field of e-commerce and trade; determine the current state and features of e-trade in the enterprise management system; determine the key trends in the development of e-trade in the field of modern marketing concepts; determine directions of e-trade development. Certain contradictions in the international trade business led to the unification of standards in 80s, and later in the 90s there were changes in the standard, which was already based on Internet technologies. It was proved that е-trade as part of e-commerce is a source of competitive advantage for the manufacturer, seller and market partners, as it provides the possibility of remote communication with market partners, reduction of costs for the organization of the sales process, operational costs, global coverage of markets and personalized marketing. For buyers, the key advantages of online shopping are convenience, speed, a wide range of products, ease of comparison and payment. Disadvantages of e-commerce are the high intensity of competition, the risk of personal data availability and the possibility of their illegal appropriation, online fraud. The introduction of electronic commerce has significantly changed the way trade enterprises work and the possibilities of interaction with consumers. An e-trade organization removes many of the barriers of traditional trade while embracing new business principles. The differences between traditional trade and e-trade are significant in communications, business flexibility, production and sales logistics, payment methods and sales parameters: e-commerce has advantages in almost all parameters. The development of e-commerce in Ukraine in the last 5 years is taking place at a rapid pace, and this trend has only intensified as a result of the pandemic, which has developed a habitual pattern of behavior to buy online. According to the structure, the lion's share of the e-commerce market in Ukraine is the sale of electronics, toys, goods for creativity, clothes, shoes and accessories. The main trends shaping the retail industry in the perspective of 2026 are the further growth of e-commerce volumes in all regions and across all product categories, the negative impact of inflation on consumer behavior and the efficiency of retail networks; digitalization, which is becoming the main area of investment for retailers; development of the 4th generation of q-commerce (electronic commerce with an emphasis on fast delivery).
Keywords: trade; e-trade; e-commerce; online sales; marketing; digitalization; global competition